The effect of early surgical treatment on functional outcomes in terrible triad of elbow: a comparative study - Acar, Barış; Çarkçı, Engin; Sert, Selman (The European Research Journal, 2023)
Objectives: In our study, we aimed to evaluate the effect of early surgical treatment on functional results in the terrible triad of the elbow. Methods: Fifty-four patients operated for the terrible triad of elbow (TTE) injuries were included in the study. The study groups were determined as Group A (operated within 24 hours) and Group B (operated after one week). The same surgical procedure and rehabilitation program were applied to all patients. The follow-up period was 16.4 ± 8.4, with a minimum of 6 months. In the last follow-up, the flexion-extension range and supination-pronation interval were evaluated. Mayo Elbow Performance Score (MEPS) and Oxford Elbow Score were used for functional scoring. Results: There was no significant difference between the two groups in terms of age, gender, injury type, and fracture classification. Elbow motion in group A was higher than in group B (p < 0.01). Moreover, group A had better higher MEPS and Oxford Elbow Score, an excellent and good rate than group B at the final clinical visit (p < 0.01). No postoperative pain or complication rate differences were found between the two groups. Conclusions: Early operation for TTE patients resulted in better functional recovery than delayed operation.